The Sage encyclopedia of children and childhood studies - Abebe, Tatek (Sage Publications. Inc., 2020)
This four-volume encyclopedia covers a wide range of themes and topics, including: Social constructions of childhood, Children's rights, Politics/representations/geographies, Child-specific research methods, Histories of childhood/Transnational childhoods, Sociology/anthropology of childhood theories and Theorists key concepts. This interdisciplinary encyclopedia will be of interest to students and researchers in: Childhood studies, Sociology/Anthropology, Psychology/Education, Social Welfare, Cultural studies/Gender studies/Disabilty studies